Diode laser – A cure for obstinate oral lichen planus: A case series and review of the literature - Sonawane, Shrutika; Sawane, Harshawardhan; Pasalkar, Lavanya; Khare, Vikram (Indian Journal of Case Reports, 2022)
Oral lichen planus (OLP) is a chronic T-cell mediated inflammatory disease of unknown etiology. Hence, no gold standard treatment modalities are available. Due to therapeutic challenges offered by conventional therapy, there is a need for effective alternate treatment with minimal side effects. The development of lasers has brought light to the treatment of obstinate OLP. Three cases of male patients in the age group 30–40 years complaining of a burning sensation in the mouth have been mentioned. Clinical and histopathological investigations showed typical findings of OLP. The treatment was started with conventional therapy of corticosteroids. The symptoms were assessed on the visual analog scale (VAS) and showed marked reduction but without complete alleviation. Hence, ablation of the lesion using a 980 nm soft-tissue diode laser was planned. The outcome of the treatment was successful, VAS 0, and no recurrence occurred in 11 months follow-up. The results of a 980 nm diode laser for the treatment of OLP are satisfactory and should be considered as a treatment alternative to conventional remedies.